ChemInform Abstract: Synthesis of Novel Isoxazolo[2", 3":1′, 2′]pyrimido[4′, 5′:4, 5]pyrimido [6, 1‐b]quinazoline‐8‐ones and Their in vitro Anticancer and Antimicrobial Activities. Issue 15 (April 2015) - Rajanarendar, E.; Kishore, B.; Ramakrishna, S.; Nagaraju, D.; Venkateshwarlu, P.
Abstract: Compounds (VIIb) and (VIIc) show potent anticancer and antimicrobial activities comparable to the standard drugs.